ANALISIS KONSEP KURIKULUM MERDEKA DALAM PENDIDIKAN DI INDONESIA - Hutabarat, Keren Hapug; Luhukay, Michelya Zabrina; Putri. A, Zaskia Rachmadini; Iskandar, Sofyan (Pedagogik : Jurnal Pendidikan Guru Sekolah Dasar, 2025)
The Merdeka Curriculum is a recent educational reform initiative in Indonesia aimed at granting greater autonomy to schools and teachers in designing learning processes that align with students’ needs and contextual realities. This curriculum emphasizes student-centered learning, flexibility, and character development through the Profil Pelajar Pancasila (Pancasila Student Profile). This article analyzes the core concepts of the Merdeka Curriculum, its key components such as Contextual Learning, and the crucial role of teachers in its implementation. The study finds that the success of the Merdeka Curriculum heavily depends on teachers’ understanding, school infrastructure readiness, and collaboration among stakeholders. Despite facing challenges—particularly in resource-limited areas—the curriculum has strong potential to foster meaningful and relevant learning suited to 21st-century demands.